Empowering Traditional Culinary Msmes Through Business Plan Development Assistance In Panumbangan District, Tasikmalaya - R. Hozin Abdul Fatah; Siti Amirah Makarim; Lati Sari Dewi; Fitriani; Wadini; Syaeful Hilal (CV. SINAR HOWUHOWU, 2025)
Micro, Small, and Medium Enterprises (MSMEs) in the culinary sector contribute significantly to the local economy in Tasikmalaya. However, many culinary entrepreneurs, especially those producing traditional food products in Panumbangan District, face challenges in preparing structured and sustainable business plans. This community engagement program aims to provide technical assistance and training for culinary MSME actors in developing comprehensive business plans tailored to their specific business contexts. Using a participatory approach and the IPOO (Input–Process–Output–Outcome) framework, this program involved needs assessment, training workshops, practical mentoring, and business plan development. The results showed increased awareness, knowledge, and skills among participants in creating and implementing business plans. The outcomes also indicate a positive shift in participants' readiness to apply strategic planning for business growth. This program proves that systematic and context-based assistance can empower local MSMEs and strengthen their sustainability in the regional creative economy.